METEOROLOGICAL DATA AT MIZUHO STATION, ANTARCTICA IN 1982 - TAKAHASHI, Shuhei; OHMAE, Hirokazu; ISHIKAWA, Masao; KATSUSHIMA, Takayoshi; NISHIO, Fumihiko (National Institute of Polar Research, 1983)
P(論文) departmental bulletin paper